The Uniqueness of Japanese Passive Voice -A New Approach to Understanding Japanese Passive Voice- - Andi Irma Sarjani (Future Science, 2021)
Japanese passive sentences structurally include “direct passive sentences” which have their equivalent in active sentences, and “indirect passive sentences” which have no equivalent in active sentences. Direct passive is expressed by the prefix “di-“ in Indonesian passive sentence, but indirect passive cannot be expressed by the prefix “di-“ and it seems difficult for Indonesian Japanese learners. Indirect passive does not exist in many languages, including in English and somehow in the Indonesian language, too. This paper aims to know why do Japanese people use passive voice to convey events or incidents, what functions does the passive distraction voice have different from the active voice, and to clarify about the differences and similarities between Japanese and Indonesian passive sentences. These points may be obvious to Japanese native speakers in some sense, but it will be such a great difficulty for Indonesian learners of Japanese to learn and use. Through this paper result, in which using a descriptive-qualitative method, there are four main conditions in Japanese direct passive sentences, namely the speaker’s point of view, conditions for changing conditions, conditions for specificity, and conditions for losses. In Japanese, if one of the four conditions has been fulfilled (or two or more conditions), then the passive voice can be accepted. Also, Japanese learners must understand that sentences with the Indonesian prefix “di-“ do not automatically become passive sentences in Japanese. If these important points are not well known or understood, this can lead to misunderstandings in the use of Japanese passive voice.